Fetal aorta larger than the main pulmonary artery on the three‐vessel view: Correlation with postnatal echocardiographic findings. Issue 7 (18th March 2016) - Idilman, Ilkay S.; Ipek, Ali; Balaban, Mehtap; Keskin, Huseyin Levent; Aypar, Ebru; Ozkutlu, Suheyla
ABSTRACT: Purpose: This study investigated postnatal cardiac anomalies determined by postnatal echocardiography in fetuses with the ascending aorta (AA) diameter larger than that of the main pulmonary artery (MPA) on the three‐vessel view (3VV). Methods: The study included 17 pregnancies. The diameters of the AA and MPA were assessed on the 3VV in second‐trimester sonographic screening, and all the patients underwent postnatal echocardiography to assess the cardiac outcome. Results: In the study population, the mean AA diameter was 3.7 mm (range, 2.2–5.6 mm), and the mean MPA diameter was 3.2 mm (range, 1.8–5.2 mm). The mean AA/MPA ratio was 1.2 (range, 1.1–1.9). According to the postnatal echocardiograms, one of the patients had tetralogy of Fallot. This patient had the highest prenatal AA/MPA ratio (1.9). Among the remaining 16 cases, five had secundum atrial septal defects, with two having concomitant dilatation of the AA. There was one case of isolated dilatation of the AA. Conclusions: Although an AA with a diameter larger than that of the MPA on the 3VV does not usually indicate severe congenital heart disease involving the ventricular outflow tract and/or great arteries, careful prenatal and postnatal echocardiographic examinations are mandatory to determine the presence of congenital heart disease. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 44 :423–428, 2016;